Next level grammar for a digital age: Teaching with social media and online tools for rhetorical understanding and critical creation. (2022) - Lim, Kyu Yun (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2024)
Next level grammar for a digital age by Darren Crovitz, Michelle D. Devereaux, and Clarice M. Morgan has made a valuable contribution to English Language Arts (ELA) education by delineating how grammar instruction can be situated within real-life contexts using digital technologies and media, as well as emphasizing the importance of critical digital literacy in ELA education. The book provides educators with a wide range of approaches to guide students in utilizing language in digital spaces and understanding rhetorical grammar to create digital content, aiming to raise learners to become more conscious digital readers and writers and to grow up to be engaged citizens. With its concrete and practical lesson ideas, the book helps language teachers to prepare for teaching complex and challenging topics that emerge in digital realms and to guide students to incrementally develop their literacy skills. Individuals in language education will find valuable insights for engaging discussions on how language teaching can be updated to meet requirements of an increasingly digital media landscape.